2007
DOI: 10.4103/0970-1591.33731
|View full text |Cite
|
Sign up to set email alerts
|

Stress urinary incontinence after male to female gender reassignment surgery: Successful use of a pubo-vaginal sling

Abstract: The case of a 50-year-old patient who had undergone male to female gender reassignment surgery is presented. She presented with mixed incontinence with symptoms of stress incontinence predominating. Initial conservative treatment was unsuccessful and subsequent videourodynamic assessment demonstrated urodynamic stress incontinence in association with a partially open bladder neck at rest. Also noted during the study was cough-induced detrusor overactivity. The option of inserting a pubo-vaginal sling using aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Urge and stress incontinence were reportedly observed post MtF GRS, however, documentation, evaluation and intervention for these complaints was not well elucidated. Commonly reported functional urinary problems after vaginoplasty include stress, urinary incontinence or urgency symptoms (66%), obstruction (33%), and urinary tract infections (2%) (Lawrence, ; Dangle and Harrison, ; Goddard et al, ; Amend et al, ). In a study comparing FtM versus MtF, Hoebeke et al () found that while less urinary changes were present in the MTF group than the FtM, the major change for MtF was incontinence, present in 16% of patients with urge, stress, and mixed urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…Urge and stress incontinence were reportedly observed post MtF GRS, however, documentation, evaluation and intervention for these complaints was not well elucidated. Commonly reported functional urinary problems after vaginoplasty include stress, urinary incontinence or urgency symptoms (66%), obstruction (33%), and urinary tract infections (2%) (Lawrence, ; Dangle and Harrison, ; Goddard et al, ; Amend et al, ). In a study comparing FtM versus MtF, Hoebeke et al () found that while less urinary changes were present in the MTF group than the FtM, the major change for MtF was incontinence, present in 16% of patients with urge, stress, and mixed urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…Levator spasm as a result of surgical reconstruction may lead to pain and voiding changes (43). Surgical remedies for post-GGAS stress incontinence, for example, are not well studied and limited to case reports (44,45).…”
Section: Incidence Of Urinary Symptoms After Ggasmentioning
confidence: 99%